Effect of the stress distribution in simple welded specimens and complex components on the crack propagation life. (November 2016) - Fischer, C.; Fricke, W.
Highlights: Slow crack propagation in complex welded components was confirmed by simulations. The stress gradient, the effective plate thickness and the notch effect have an impact. Examples show an increase in life of almost two between specimens and components. The common stress-based fatigue parameters consider the effects only partly. Abstract: While a long stable crack propagation phase was observed during experiments of complex welded components, very conservative estimations of the fatigue life were achieved in the past. The difference was explained by the stress gradient occurring over the plate thickness. This paper deals with numerical crack propagation simulations which were performed for geometrically different variants. The variants differ in global geometry, boundary conditions and weld shape. The analyses aim to investigate how the crack propagation is altered if the structural configuration gets more complex. In conclusion, the stress gradient over the plate thickness, the effective plate thickness due to vertical web plates and high notch effects slow down the crack propagation rate if the same stress value being effective for fatigue appears at the weld toe. Thereby, the load-carrying grade of the weld, the weld flank angle and the geometrical configuration also have an impact on both the notch effect and the local stress concentration.